Analysis by real-time PCR of five transport and conservation mediums of nasopharyngeal swab samples to COVID-19 diagnosis in Santiago of Chile - Barrera Avalos, Carlos.; Luraschi, Roberto; Vallejos Vidal, Eva Carolina.; Figueroa, Maximiliano; Arenillas, Esteban; Barría, Daniela; Hernández, Felipe; Mateluna Flores, Carlos.; Mena, Javier; Rioseco, Claudia; Torrent, Claudia; Vergara, Claudio; et al. (John Wiley and Sons Inc, 2022)
Due to the COVID‐19 pandemic, many transport kits have been manufactured to pre- serve and transport nasopharyngeal swab samples (NPSs) from patients. However, there is no information on the performance of the different virus transport media (VTM) used in COVID‐19 diagnosis in the population of Santiago de Chile. We compared the RT‐qPCR amplification profile of five different viral transport kit mediums, including DNA/RNA ShieldTM, NAT, VTM‐N, EzmedlabTM, and phosphate‐buffered saline (PBS), for NPSs from Central Metropolitan Health Service, Santiago, Chile. The DNA/RNA ShieldTM medium showed a better performance in terms of Cq and RFU values for the internal reference RNase P and viral ORF1ab probes. By contrast, the PBS transport medium registered higher Cq values for the viral and reference gene, compared to the other VTM. DNA/ RNA ShieldTM shows higher relative fluorescence units (RFUs) and lower Cq values for the reference gene. Collectively, our results suggest that the PBS medium could compromise the sample diagnosis because of its lower RT‐qPCR performance. The NAT, Ezmedlab and VTM‐N, and DNA/RNA ShieldTM media show acceptable RT‐qPCR parameters and, consequently, seem suitable for use in COVID‐19 diagnosis.
Keywords: False negative diagnostic; Nasopharyngeal sample transport kits; RNA subunit of ribonuclease P (RNase P) amplification; SARS‐CoV‐2 diagnostics; SARS‐CoV‐2 ORF1ab gene; Virus transport medium; COVID-19 (Disease)